32 - TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) APLICATION AS ANALGESY TECHNIQUE DURING POST-OPERATORY PHYSIOTHERAPY IN PATIENTS WITH TOTAL HIP ARTHROPLASTY (Fiep Bulletin - online, 2011)
Total Hip Arthroplasty (THA) is a common procedure in the present time, especially due to the raise of the population's life expectancy. Elderly patients are great candidates to this surgical procedure and also very vulnerable, in relation to the surgery risks themselves, just like the action of the medicine in the post-operatory. Non-pharmacological resources such as the Transcutaneous Electrical Nerve Stimulation (TENS) are being greatly studied and used by physiotherapy in post-surgical patients. This research's main objective was to verify the influence of the TENS as coadjutant in the cemented THA post-operatory pain relief. The sample (n=23) was consisted of patients in the first post-operatory day of hip arthroplasty, between 60-80 years old, that were divided into two groups, the control group (n=11) received placebo treatment and the treatment group (n=12) received effective electric analgesia. Both groups received the same medicinal therapy, health care routine and physiotherapeutic protocol. The pain was measured through the visual analog pain scale and the McGill pain questionnaire in 3 steps (in the first and second post-operatory days); before the TENS application, immediately after the application of this resource, and after the physiotherapy (made after the TENS). As an indirect way of evaluating the analgesia, it was also registered the quantity of demanded analgesic medicine of each group. The results show that the treatment group showed enhancement of the pain levels (p>0,05), just as less necessity of analgesic medicine administration, what allows to conclude that the TENS is an efficient coadjutant resource in the post-operatory analgesia during the physiotherapy in elders submitted to THA.
Keywords: Analgesia; Arthroplasty; Replacement; Hip; Transcutaneous Electric Nerve Stimulation